ASESMEN FORMATIF BERBASIS GROWTH MINDSET UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DIAGRAM MATERI PENYAJIAN DATA KELAS II - Tukiyo; Febrianti, Ismaya; Trian Adilla, Diva; Dwi Apriliana , Fariza; Raikhan, Ayu; Nur Sekar Sari, Devita; Afif Fadilah, Erizal; Wijayanti, Septiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to interpret pictographs is an essential component of data literacy that should be developed from the elementary school level, as it enables students to understand, compare, and process data presented in visual form. However, classroom observations in Grade II at SDN 4 Bareng Lor indicated that many students experienced difficulties in interpreting, comparing, and processing data from pictographs and lacked confidence in learning mathematics. This study aimed to describe the implementation of a growth-mindset-based formative assessment and to improve the pictograph interpretation skills of Grade II students at SDN 4 Bareng Lor. The study employed the Kemmis and McTaggart Classroom Action Research (CAR) model, which was conducted in two cycles. The participants consisted of 34 second-grade students in the 2025/2026 academic year. Data were collected through classroom observation, formative assessment, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques, complemented by Normalized Gain (N-Gain) analysis. The findings revealed that the growth-mindset-based formative assessment was implemented through group discussions, student presentations, feedback, and learning reflection. The implementation of this assessment significantly improved students' pictograph interpretation skills across all indicators. Students' ability to interpret pictographs increased from 72.06% to 90.44% (N-Gain = 0.66, medium category), their ability to compare data improved from 70.65% to 87.26% (N-Gain = 0.57, medium category), and their ability to process data increased from 55.94% to 88.26% (N-Gain = 0.73, high category). By the end of the second cycle, all indicators had achieved a mastery level exceeding 80%. Therefore, growth-mindset-based formative assessment was effective in improving the pictograph interpretation skills of Grade II students at SDN 4 Bareng Lor.